Lack of Association between LOXL1 Variants and Primary Open- Angle Glaucoma in Three Different Populations - Yutao, L.; Schmidt, S.; Qin, X.; Gibson, J.; Hutchins, K.; Santiago-Turla, C.; Wiggs, J.L.; Budenz, D.L.; Akafo, S.; Challa, P.; Herndon, L.W.; Hauser, M.A.; et al. (Investigative Ophthalmology & Visual Science, 2008)
Purpose—Significant association has recently been reported between pseudoexfoliation glaucoma (XFG) and two single-nucleotide polymorphisms (SNPs), rs3825942, and rs1048661, in the lysyl oxidase-like 1 gene (LOXL1). The purpose of this study was to investigate whether XFG-associated variants of LOXL1 play a significant role in primary open-angle glaucoma in the Caucasian, African- American, and Ghanaian (West-African) populations. Methods—POAG was defined as the presence of glaucomatous optic nerve damage, associated visual field loss, and elevated intraocular pressure (>22 mm Hg in both eyes). Thirteen tagging SNPs were genotyped by allelic discrimination assays in the Caucasian (279 cases and 227 controls), African-American (193 cases and 97 controls), and Ghanaian (170 cases and 138 controls) populations. Allele and genotype frequencies were compared between the cases and controls from each population. Results—None of the SNPs associated with XFG in LOXL1 were significantly associated with POAG in these populations. The risk allele frequencies for rs2165241 and rs3825942 were significantly lower in the African-American and Ghanaian populations, compared with Caucasian individuals. Conclusions—There was no association between SNPs in the LOXL1 gene and POAG. This is the first analysis of the LOXL1 gene in African-American and West-African populations. LOXL1 gene variants do not appear to play a significant role in the pathogenesis of POAG in populations of either Caucasian or West-African ancestry. Primary open-angle glaucoma (POAG, OMIM 137760